A broadband metamaterial damper design based on synergetic coupling among multi-cells. (April 2023) - Wang, Xingzhong; Pang, Yatong; Hui Wu, Jiu; Ma, Fuyin
Highlights: A broadband damper design method to achieve broadband vibration absorption performance by superposition of the working bands of several damping units is proposed. A linear superposition of the absorption bandwidth is realized by integrating the units with band gaps in different frequency ranges in parallel. This design belongs to a special metamaterial-based MDOF damper that could satisfy both low damping ratio and weak coupling conditions. The working bandwidth of each sub-unit could be optimized by changing structural parameters and structural forms. The sizes of the damper device and each sub-unit are sub-wavelength, so the additional mass is greatly lower than that of the traditional DVA. Abstract: This paper proposes a broadband damping method to achieve broadband vibration absorption by superposition of the working bands of several damping units. The device composes of several local resonant metamaterial dampers with gradient elastic wave band gaps via weak coupling. By integrating the units with band gaps in different frequency ranges in parallel, a linear superposition of the absorption bandwidth can be achieved. This property overcomes the shortcomings of the traditional dynamic vibration absorbers (DVAs) or metamaterial dampers with narrow working bands, and provides a solution for broadband low-frequency vibration attenuation. Compared to conventional multi-degree-of-freedom (MDOF) DVAs, this design belongs to a special metamaterial-based MDOF damper that could satisfy both low damping ratio and weak coupling conditions. As the working bandwidth of each sub-unit could be optimized by changing structural parameters and structural forms, the available design parameters are significantly increased. Moreover, the sizes of the damper device and each sub-unit are sub-wavelength, so the additional mass is greatly lower than that of the traditional DVA. The design method and device proposed in this paper are expected to be widely used in the broadband low-frequency vibration suppression of various types of machinery and equipment.